Factors Influencing Whistleblowing Intention among Accounting Students in Indonesia - Sany, Sany; Darmasaputra, Alan; Alim, Cathrine Cecilia; Niko, Ferdinand (International Journal of Organizational Behavior and Policy, 2024)
The study aimed to determine the effect organizational commitment, subjective norms and group cohesion to whistleblowing intention of accounting students in Indonesia. Data was collected using a questionnaire administered using Google Form. The study’s sample was 218 accounting students from various universities in Surabaya, Indonesia. This study results show that high organizational commitment, subjective norms, and group cohesion increase whistleblowing intention among participants studied. Limitations include the limited number of universities surveyed for respondent recruitment, suggesting the need for additional data collection methods. This study is original in its investigation of the relationships between organizational commitment, subjective norms, group cohesion, and whistleblowing intention among accounting students in Surabaya.